AI Orchestration at the Individual Scale_Systematic Methodology and Verified Outcomes v1.4 - Browne, Emmanuel (Zendo, 2025)
This work situates Individual-Scale AI Orchestration (I.S.A.O.) within a broader Interactive Intelligence Systems (IIS) framework, wherein intelligence is treated as an emergent property of structured interaction between humans and non-deterministic computational systems. Within this framework, Adaptive Intelligence Systems (AIS) describe systems whose effective performance depends not solely on internal model capability, but on feedback, verification, and decision authority distributed across human–AI interaction loops. Rather than proposing a new discipline, this paper formalizes I.S.A.O. as a methodological framework for operationalizing such interactions under uncertainty, providing reproducible structures for orchestration, validation, and convergence across heterogeneous AI systems. Over an approximately 19-month development period (June 2024–January 2026), the methodology was validated through four externally verifiable outcomes: (1) CompTIA Security+ certification achieved through Persona-Hybrid-Agent (PHA) tutoring; (2) ISC2 CC certification achieved through the same methodology; (3) successful resolution of a multi-year federal student loan default through orchestrated financial guidance; and (4) the recursive completion of this peer-reviewable manuscript using I.S.A.O. itself — providing a self-referential demonstration of methodological efficacy. The core contribution of this work is a distributed, vendor-agnostic orchestration protocol that integrates ChatGPT, Claude, Copilot, and Grok into a heterogeneous, fault-tolerant Distributed Intelligence Mesh System (D.I.M.S.). Real-world stress tests — including platform-level disruptions at Anthropic (November 2025) and xAI (December 2025) — demonstrated 32-minute operational recovery and validated cross-LLM redundancy as structurally necessary for uninterrupted independent AI research continuity. The full system was developed on a mid-tier laptop and utilized ~$260.00 in AI subscriptions, demonstrating that methodology, not computational scale, is the true bottleneck in independent AI innovation. I.S.A.O. provides the first end-to-end, pedagogically scalable framework for individual researchers, students, and resource-constrained environments seeking to conduct structured, publication-grade AI research.
Keywords: Artificial Intelligence; Computer Science; Human Computer Interaction; Information Systems; Research Methodology